Reduction of Broiler House Malodor by Direct Feeding of a Lactobacilli Containing Probiotic - Chang, M.H.; Chen, T.C. (International Journal of Poultry Science, 2003)
Studies were conducted to investigate the direct feeding of a lactobacilli containing probiotic, Ecozyme, on broiler house malodor. Results indicated that feeding a diet containing the probiotic decreased (P<0.05) the environmental ammonia level in broiler house as well as pH and moisture content of excreta during the growth period. Gas chromatography/mass spectrometry data indicated that the quantity of volatile malodor compounds was much lower for the house with birds fed a diet containing lactobacilli than those of the controls. Volatile compounds such as 1-propanol, 1-butanol, 3-methyl hexane, 2-methylhoptane, dimethyl benzene, 3-methylheptane, octane, 2, 4-dimethyl hexane and octamethylcydotetrasiloxane were decrease to an undetectable level in the treatment room. Many major malodor indicators such as 2-butanone, hexanal, dimethyl disulfide and dimethyltrisulfide were also reduced by the feeding of lactobacilli containing diet. All 16 sensory panelists detected the odor difference between the treatment and control rooms. The control room has a higher malodor score than those of the treated one.